An Analysis of Language Style in Little Buddha Movie - Swantara, Made; Suastini, Ni Wayan; Santika , I Dewa Ayu Devi Maharani (Institut Pariwisata dan Bisnis Internasional, 2024)
This study focused on the use of language style in the movie